TEACHER'S METHOD IN PROVIDING LESSON LEARNING IMPROVEMENT TO STUDENTS - Zainudin; Zaimudin (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2021)
There are still many teachers who are not professional in teaching various subjects, so that students' learning motivation is still low. Students still need encouragement in learning, it is necessary for teachers to provide motivation to their students with the aim that these students have a higher spirit in an effort to improve their achievements. Teachers as mentors are expected to be able to create strategic conditions that can make students comfortable in following the learning process. In creating good conditions, teachers should pay attention to two things: first, internal conditions are conditions that exist in the students themselves, such as health, safety, tranquility, and so on. Second, external conditions are conditions that exist outside the human person, for example the cleanliness of the house, lighting and other physical environmental conditions. To be able to study effectively, a good and orderly physical environment is needed, for example, the study room must be clean, there are no odors that can interfere with learning concentration, the room is bright enough, not dark and does not interfere with the eyes, the facilities needed for learning are sufficient or complete.